Thirteen Women Strong : The Making of a Team - Wallace, Robert K., 1944- (Book collections on Project MUSE., 2008)
'Thirteen Women Strong' chronicles the 2006-2007 season of the Northern Kentucky University women's basketball team. Including compelling interviews with the players themselves, this work welcomes readers into the lives of young women whose world is made up of equal parts pressure and accomplishment.